Fairness in international law and institutions - Franck, Thomas M. (Oxford : Clarendon Press ; New York : Oxford University Press, 1995)
International Law has developed dramatically during the past few decades alongside numerous international institutions. This book sheds new light on traditional elements of international law and serves as an introduction to the new law and multilateral institutions concerned with issues such as global security, economic development, environmental protection, and self-determination. The central purpose of the book, however, is not simply to inform the reader about recent developments, but to attempt a critique of their fairness. To that end, the author develops a theory of fairness that draws on historical, philosophical, and sociological sources. Within the concept of fairness, the author contends that developed notions of justice and legitimacy reflect society's ambiguities regarding the right balance between change and order.
This book, based on Professor Franck's Hague Academy General Course, offers a critical analysis of the prescriptive norms and institutions of modern international law has the capacity to advance, in practice, the abstract social values shared by the community of persons and states.
Ch. 1. Fairness and International Law: An Analytical Framework -- Ch. 2. Legitimacy and Fairness -- Ch. 3. Equity as Fairness -- Ch. 4. Fairness to Persons: The Democratic Entitlement -- Ch. 5. Fairness to 'Peoples' and their Right to Self-Determination -- Ch. 6. Administrative Impartiality as Fairness: The UN Secretary-General's Good Offices and Other 'Third Party' Functions -- Ch. 7. The Bona Fides of Power: Security Council and Threats to the Peace -- Ch. 8. Just and Unjust War -- Ch. 9. Collective Security: Sharing Responsibility and Burdens -- Ch. 10. Judicial Fairness: The International Court of Justice -- Ch. 11. Law, Moral Philosophy, and Economics in Environmental Discourse -- Ch. 12. Some Instances of Fairness in Establishing Environmental Normative Systems -- Ch. 13. Economic Fairness: Terms of Development and Trade -- Ch. 14. Fairness in International Investment Law -- Ch. 15. Forums of Fairness.
Includes bibliographical references and index.
Keywords: International law -- Philosophy; Fairness; Justice; Social justice; Fairness; International law -- Philosophy; Justice; Faires Verfahren; Fairness; International law -- Philosophy; Fairness; International law -- Philosophy; Justice